2005
DOI: 10.1007/s00421-005-1348-x
|View full text |Cite
|
Sign up to set email alerts
|

Human thermoregulatory function during exercise and immersion after 35 days of horizontal bed-rest and recovery

Abstract: The present study evaluated the effect of 35 days of experimental horizontal bed-rest on exercise and immersion thermoregulatory function. Fifteen healthy male volunteers were assigned to either a Control (n = 5) or Bed-rest (n = 10) group. Thermoregulatory function was evaluated during a 30-min bout of submaximal exercise on a cycle ergometer, followed immediately by a 100-min immersion in 28 degrees C water. For the Bed-rest group, exercise and immersion thermoregulatory responses observed post-bed-rest were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 30 publications
2
21
0
Order By: Relevance
“…Inappropriate behavioural regulation of body temperature may contribute, at least in part, to the observed thermal imbalance during prolonged bed rest or microgravity. Changes in thermal comfort and thermal sensation have been reported in previous studies during hypokinesia (Panferova 1976(Panferova , 1989) and experimental bed rest (Fortney et al 1996;Greenleaf 1989;Mekjavic et al 2005). However, the eVects of bed rest on behavioural thermoregulatory responses have not yet been investigated.…”
Section: Introductionmentioning
confidence: 80%
See 2 more Smart Citations
“…Inappropriate behavioural regulation of body temperature may contribute, at least in part, to the observed thermal imbalance during prolonged bed rest or microgravity. Changes in thermal comfort and thermal sensation have been reported in previous studies during hypokinesia (Panferova 1976(Panferova , 1989) and experimental bed rest (Fortney et al 1996;Greenleaf 1989;Mekjavic et al 2005). However, the eVects of bed rest on behavioural thermoregulatory responses have not yet been investigated.…”
Section: Introductionmentioning
confidence: 80%
“…In addition, since activation of behavioural thermoregulatory responses relies on similar thermal aVerent neural information as autonomic thermoregulatory responses, it was hypothesised that behavioural responses might also be aVected in such conditions. Mekjavic et al (2005) reported that subjects perceived similar combinations of skin and the core temperatures as warmer and thermally less uncomfortable after 35 days of horizontal bed rest. Reports from earlier studies indicate that some changes in thermal sensitivity occur (Fortney et al 1996;Panferova 1976) and that subjects in bed rest studies often complain of cold feet (Fortney et al 1996;Mekjavic et al 2005;Taylor et al 1949).…”
Section: Evects Of Bed Rest On Thermoregulationmentioning
confidence: 97%
See 1 more Smart Citation
“…Video surveillance and results from criterion tests and other experiments indicated that all subjects complied with the requirements of the bedrest protocol (Mekjavic et al 2005;Berg et al 2007;Eiken et al 2008). Prior to bedrest, all ten subjects could endure the 10-min stand test with normal cardiovascular responses and without experiencing any unwarranted symptoms.…”
Section: Methodological Considerationsmentioning
confidence: 93%
“…Results from these criterion tests have, for the most part, been reported in detail elsewhere (cf. Mekjavic et al 2005;Berg et al 2007;Eiken et al 2008). …”
Section: Criterion Testsmentioning
confidence: 97%